2015
DOI: 10.1108/jpif-08-2014-0054
|View full text |Cite
|
Sign up to set email alerts
|

Defining the three Rs of commercial property market performance

Abstract: Purpose – Modern property investment allocation techniques are typically based on recognised measures of return and risk. Whilst these models work well in theory under stable conditions, they can fail when stable assumptions cease to hold and extreme volatility occurs. This is evident in commercial property markets which can experience extended stable periods followed by large concentrated negative price fluctuations as a result of major unpredictable events. This extreme volatility may not be … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 8 publications
0
10
0
Order By: Relevance
“…Furthermore, it is observed that in developed nations (United States of America, UK, Australia, etc. ), property investment performance indices are constructed monthly or quarterly to produce a robust data set (Higgins, 2015;MSCI, 2020). This allows for the capture of the real estate market cycle or an outlier occurrence within a year; annual averages may not properly capture the real estate market cycle.…”
Section: Some Issues Plaguing Investment Analysis In Lagos Metropolismentioning
confidence: 99%
“…Furthermore, it is observed that in developed nations (United States of America, UK, Australia, etc. ), property investment performance indices are constructed monthly or quarterly to produce a robust data set (Higgins, 2015;MSCI, 2020). This allows for the capture of the real estate market cycle or an outlier occurrence within a year; annual averages may not properly capture the real estate market cycle.…”
Section: Some Issues Plaguing Investment Analysis In Lagos Metropolismentioning
confidence: 99%
“…The author of this research shares the view of Briguglio and colleagues (2009) on economic vulnerability and resilience; they define economic vulnerability as the exposure of an economy to exogenous shocks; and economic resilience as the policy-induced ability of an economy to withstand or recover from the effects of such shocks. Good governance is essential to provide an economic mechanism to eliminate or ease adverse shocks caused, for example, by business cycles to enhance the level of economic resilience together with strong macroeconomic stability (Hill et al, 2008;Stevenson et al, 2014).…”
Section: Resilience and Volatilitymentioning
confidence: 99%
“…The next step is to calculate the standard deviation (Lim et al, 2008) for these periods to provide information about the volatility or stability of market movements during each examined timeframe. The assumption of the normal distribution (Jorion, 1996;Higgins, 2015) is employed to analyse the results of the standard deviations derived from the data set.…”
Section: Economic Resilience and Investment Riskmentioning
confidence: 99%
“…Property market models have the overriding aim of predicting reasonable estimates of key dependent variables: demand, supply, rent, returns, yield, vacancy, and cashflows based on information at hand (Brooks and Tsolacos, 2000, 2001Chaplin, 1998Chaplin, , 1999Chaplin, , 2000Matysiak and Tsolacos, 2003). The changes of these variables can be quantified by the internal and the external determinants within which the decisions are made in the market (Higgins, 2000). The interlinked commercial property markets set out economic relationships that are most relevant to the forecasting models.…”
Section: Commercial Property Market Forecastingmentioning
confidence: 99%